2011
DOI: 10.3390/d3030329
|View full text |Cite
|
Sign up to set email alerts
|

Species Richness and Community Structure on a High Latitude Reef: Implications for Conservation and Management

Abstract: Abstract:In spite of the wealth of research on the Great Barrier Reef, few detailed biodiversity assessments of its inshore coral communities have been conducted. Effective conservation and management of marine ecosystems begins with fine-scale biophysical assessments focused on diversity and the architectural species that build the structural framework of the reef. In this study, we investigate key coral diversity and environmental attributes of an inshore reef system surrounding the Keppel Bay Islands near R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 90 publications
0
15
0
Order By: Relevance
“…The period 1998 to 2010 is defined predominantly by thermal bleaching in the earlier years and flooding of the Fitzroy River in the later years (Figures and S6; Berkelmans et al, ; Elvidge et al, ). While coral bleaching was observed in 1998 and 2002, post bleaching assessments reported little total coral mortality in the Keppel Islands (Jones et al, ; Maynard et al, ; van Oppen et al, ). The lack of death assemblage dating to this period supports observations that corals were able to recover from bleaching via tissue regeneration (Diaz‐Pulido et al, ), with little destruction of the original framework.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The period 1998 to 2010 is defined predominantly by thermal bleaching in the earlier years and flooding of the Fitzroy River in the later years (Figures and S6; Berkelmans et al, ; Elvidge et al, ). While coral bleaching was observed in 1998 and 2002, post bleaching assessments reported little total coral mortality in the Keppel Islands (Jones et al, ; Maynard et al, ; van Oppen et al, ). The lack of death assemblage dating to this period supports observations that corals were able to recover from bleaching via tissue regeneration (Diaz‐Pulido et al, ), with little destruction of the original framework.…”
Section: Discussionmentioning
confidence: 99%
“…The modern reef slope drops rapidly to a sandy base at a depth of 7 mLAT and is dominated by fast growing arborescent Acropora spp. with generally high coral cover (~60%); however, the region experiences frequent disturbance events that periodically affect coral cover dynamics (Jones et al, 2011;Kennedy et al, 2018;van Woesik & Done, 1997). Notable recent disturbance 10.1029/2019PA003768 Paleoceanography and Paleoclimatology events include up to 100% coral mortality due to flooding in 1991 ( Van Woesik, 1991) andsubstantial thermal bleaching in 1998substantial thermal bleaching in , 2002substantial thermal bleaching in (Elvidge et al, 2004, and 2006; mild to moderate bleaching in 2016 (Kennedy et al, 2018); and observed cyclone damage in 1976 and 2015.…”
Section: Site Descriptionmentioning
confidence: 99%
See 2 more Smart Citations
“…Regardless of the cause, the risk is that without timely and prolonged restrictions on harvest there could be a risk of further population declines. Since these species are already sparse and occur in small, isolated populations in the first place [35,57] there could be an "Allee" effect on the capacity of such a small population to regenerate [58,59].…”
Section: (A) (B)mentioning
confidence: 99%